1976
DOI: 10.1128/jb.128.2.536-539.1976
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-sensitive mutant of Schizosaccharomyces pombe exhibiting enhanced radiation sensitivity

Abstract: A conditional lethal and radiation-sensitive mutant of Schizosaccharomyces pombe is described in which both characteristics result from a single gene mutation. Confirmation of the pleiotropic nature of this mutant was obtained by tetrad analysis and by testing the radiation sensitivity of a large number of revertants that grew normally at the restrictive temperature. The colony-forming ability of the mutant after ultraviolet radiation, gamma radiation, and ethyl methane sulfonate treatment is considerably alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Pulse field gel electrophoresis studies reported elsewhere (24) have shown that the gene is located on the 1.2 Mb Not I fragment D (25) on chromosome 1. The complete gene is able to correct both the temperature-sensitivity of the rad4.116 mutant and its UV sensitivity (Figure 3), confirming that both these properties result from a single mutation (7). The first plasmid that we identified by its ability to complement the temperature sensitivity of the rad4.116 mutant contained a truncated gene, missing the Cterminal 37 amino acids.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Pulse field gel electrophoresis studies reported elsewhere (24) have shown that the gene is located on the 1.2 Mb Not I fragment D (25) on chromosome 1. The complete gene is able to correct both the temperature-sensitivity of the rad4.116 mutant and its UV sensitivity (Figure 3), confirming that both these properties result from a single mutation (7). The first plasmid that we identified by its ability to complement the temperature sensitivity of the rad4.116 mutant contained a truncated gene, missing the Cterminal 37 amino acids.…”
Section: Discussionsupporting
confidence: 63%
“…The cells have a very high level of sister chromatid exchanges and a reduced rate ofjoining singlestrand breaks following treatment with ionizing radiation or ethyl methanesulphonate (26). In contrast, the hypersensitivities of the rad4 mutant to UV, -y-rays and EMS were similar for each mutagen (7). No biochemical characterisation of the defect in rad4 mutants has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation in the rad4 gene of Schizosaccharomyces pombe confers sensitivity to both UV and ionizing radiation damage, as well as a temperature-sensitive phenotype (1). We previously reported the cloning of the rad4 gene (EMBL Accession no.…”
mentioning
confidence: 99%